Extensive VZV Encephalomyelitis without Rash in an Elderly Man - Karen Lynch; Prakhar Agarwal; Anu Paranandi; Susan Hadley; Mithila Vullaganti (Case Reports in Neurological Medicine)
Introduction. Varicella zoster virus (VZV) encephalomyelitis with cranial nerve involvement is rare. Characteristically it is preceded by a rash and primarily presents in the immunocompromised. The spectrum of VZV neurologic disease is extensive and it is not uncommon to present without rash. We report the case of an elderly otherwise immunocompetent patient who presented with diverse manifestations of VZV CNS infection all occurring without rash. Case Report. A 78-year-old man presented with 1 week of progressive paraparesis and sensory loss, malaise, and fevers. MRI of the neuraxis demonstrated numerous enhancing lesions: intramedullary, leptomeningeal, pachymeningeal, and cranial nerves. Cerebrospinal fluid (CSF) showed a white blood cell count of 420/μL with elevated protein (385 mg/dL). CSF VZV qualitative PCR was positive and CSF VZV immunofluorescence assay detected IgM antibody, confirming the diagnosis of VZV encephalomyelitis. Clinical and radiological improvement was observed after intravenous acyclovir treatment. Conclusion. This is a rare report of an immunocompetent patient with extensive VZV encephalomyelitis. We highlight the importance of considering this diagnosis even in the absence of the characteristic rash, and the potential risk of premature discontinuation of antiviral therapy once HSV has been excluded. Prompt recognition and treatment can dramatically reduce morbidity and mortality in patients.